A rare genetic Schuurs-Hoeijmakers syndrome (PACS1 syndrome) - T. V. Kozhanova; S. S. Zhilina; T. I. Meshcheryakova; A. D. Mikhailova; A. I. Krapivkin; N. N. Zavadenko (Эпилепсия и пароксизмальные состояния, 2024)
PACS1 neurodevelopmental disorder (Schuurs-Hoeijmakers syndrome; MIM #615009) is a rare autosomal dominant genetic syndrome characterized by developmental delay, intellectual disability, dysmorphic features, and rare seizures. The article describes a clinical case of PACS1 syndrome in a female patient with developmental delay, speech disorder, motor development delay and epilepsy coupled to described variants in PACS1 gene (rs398123009, chr11:6621120, c.607C>T, p.Arg203Trp). Knowing PACS1 syndrome molecular mechanisms is important not only for genotype-phenotypic correlation, but also for developing new therapeutic approaches that could improve the quality of patients’ life.